Spatial Planning as a Tool for Sustainable Development. Polish Realities - Waldemar Gorzym-Wilkowski (Barometr Regionalny)
Sustainable development is currently the basic philosophy of shaping socio-economic development. It seeks to ensure that the improvement of living conditions and development of the economy are reconciled and the proper conditions for the functioning of the natural environment are maintained. The achievement of such objectives requires the use of numerous and varied instruments that include spatial planning whose goals are to protect and harmonize various ways of using geographic spatial resources. The role of spatial planning as an instrument for sustainable development is appreciated in international and Polish theoretical literature. Polish legislation also states, to an increasing extent, that the need for sustainable development should be regarded as the basis of spatial development. However, the reality is that the consecutive Polish spatial planning systems have created mechanisms that have aggravated spatial conflicts, including the excessive and extensive use of space. It has resulted from the privileged position given by consecutive legal solutions to a certain category of space users at the expense of other stakeholders and the natural environment. Therefore, the effective use of spatial planning to ensure sustainable development requires the creation of a new system of planning that balances the interests of various users of space.